Poodles for dummies - Ewing, Susan M. (Hoboken, NJ : Wiley Pub., 2007)
The fun and easy way to keep your poodle healthy and happy.
Picking the poodle of your dreams -- Living happily with your poodle -- Training and having fun with your poodle pal -- Maintaining your poodle's health -- The part of tens.
Includes index.
Keywords: Poodles; Poodles -- Grooming; Poodles -- Training